Persepsi Generasi Milenial terhadap Program CSR Perusahaan Teknologi - Alfajri, Anugrah Daffa; Rahmawati, Rahmawati (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study aims to explore millennials' perceptions of Corporate Social Responsibility (CSR) programs run by technology companies. Using a qualitative approach, data was collected through in-depth interviews with ten millennial informants who have direct or indirect involvement with the CSR program. The results show that millennials have a critical view of CSR implementation, with authenticity, transparency, and long-term social impact being the main factors that influence their perceptions. Informants tend to appreciate CSR programs that are not only oriented towards the company's image, but also make a real contribution to society and the environment. In addition, millennials value the importance of their direct involvement in CSR programs through active participation, such as volunteer activities and community-based initiatives. This research concludes that technology companies need to integrate social values relevant to millennial preferences to increase the effectiveness of CSR programs and build stronger relationships with this generation.